Decreased expression of transforming growth factor-β1 and α-smooth muscle actin contributes to the protection of lotensin against chronic renal failure in rats. (15th October 2018) - Xiao, Qingfei; Guan, Yinghui; Li, Chenhao; Liu, Li; Zhao, Dan; Wang, Hongyue
Abstract: Background: Lotensin has been shown to have a protective function in the early stage of chronic renal failure. However, its role in the intermediate and late stages of chronic renal failure remains largely unknown. The present study aimed to investigate the role and underlying mechanism of lotensin in advanced chronic kidney disease. Methods: Female Wistar rats were randomly divided into three groups ( n  = 10): sham group, 5/6 nephrectomy (5/6 Nx) group, and lotensin group (oral administration of lotensin for 9 weeks following 5/6 Nx). Rats were sacrificed and pathological parameters were measured. Western blot assay and immunohistochemical staining were performed to detect the expression of transforming growth factor-β1 (TGF-β1) and α-smooth muscle actin (α-SMA) in kidney tissues. Results: Compared to the 5/6 Nx group, lotensin administration significantly decreased 5/6 Nx-induced elevation in blood urea nitrogen, serum creatinine and 24-h urinary protein excretion (UPE) rates, but markedly increased red blood cell count, plasma albumin and hemoglobin levels, along with improved renal morphology. Mechanistically, lotensin dramatically downregulated the renal expression of TGF-β1 and α-SMA induced by 5/6 Nx. Conclusions: Lotensin protects against advanced chronic kidney disease in rats with 5/6 Nx through the downregulation of TGF-β1 and α-SMA.